Emergency nurses' experience of providing care to patients who self-harm. (September 2021) - Ngune, Irene; Wynaden, Dianne; McGough, Shirley; Janerka, Carrie; Hasking, Penelope; Rees, Clare
Abstract: Background: Individuals who self-harm may present to emergency departments (EDs) for medical care. As first responders, emergency nurses can have a significant impact on the health outcomes of people who self-harm. This research explored emergency nurses' experiences of working with patients who self-harm. Methods: Data were collected using semi-structured interviews and analysed using Elo and Kyngäs' inductive content analysis. Researcher checks ensured consensus of identified categories. Adherence to the research method and inclusion of participant citations added to the trustworthiness of findings. Results: Eighteen emergency nurses from across Australia participated in the research. The category "Nurses' level of preparedness to work with people who self-harm" emerged during data analysis with four sub-categories: (1) Nurses' level of comfort to work with people who self-harm; (2) Nursing role; (3) Barriers and facilitators to providing quality care; and (4) Education and training. Conclusions: The ED is a challenging environment to provide care to people who present with self-harm. Nurses' level of comfort and attitudes towards caring for people who self-harm improved with knowledge, support and experience. Education and training in the area were important.